Artificial Intelligence and Digital Technology in Their Relation to Human Existence and Artistic Creativity - Kabier, Dr. Najla Ahmed (Thi Qar Arts Journal, 2023)
This research explores the impact of artificial intelligence and digital technologies on human existence and artistic creativity in our contemporary reality. The paper sheds light on the transformations of the relationship between humans and technology, where the study responded to questions about whether these technologies are just tools or have a deeper impact on the human experience. The paper also focused on the impact of these technologies on artistic creativity, where it was shown that artificial intelligence can be a source of inspiration for creativity, and that digital technologies provide new platforms for artistic expression. However, challenges were observed related to the importance of preserving authenticity and balance between technical and human factors in a rapidly changing society. The paper highlighted the importance of developing policies and ethical frameworks that guide the use of technologies towards enhancing human values and encouraging creativity. With a focus on developing technology that respects human identity and promotes diversity of creativity. This makes us face an approach of benefiting from technology without giving up the essential aspects of humanity and art. In short, this article highlights the importance of exploring the impact of artificial intelligence and digital technologies on human existence and artistic creativity, with a focus on the challenges and opportunities that are growing in this context. Received 10/9/2023, Accepted 28/12/2023 , Published 31/12/2023.